Formation of Fluid Inclusions during Heat Treatment of Barremo‐Bedoulian Flint: Archaeometric Implications. (15th July 2016) - Milot, J.; Siebenaller, L.; Béziat, D.; Léa, V.; Schmidt, P.; Binder, D.
Abstract : At the end of the fifth millenniumbc, the development of a specialized lithic industry in the Chassey societies of south‐eastern France and its dissemination as far as Catalonia and Tuscany attest to important socio‐economic changes in the Mediterranean Neolithic societies. The lithic production was made on barremo‐bedoulian flint that was heat‐treated to improve the sharpness of the tools produced. Microscopic observations of archaeological and geological, heated and unheated barremo‐bedoulian flint samples allowed us to highlight the heat‐induced formation of fluid inclusions. Microthermometry analyses showed that these inclusions contain pure H2 O, most probably resulting from the dehydration of length‐slow (LS) chalcedony and the closure of narrow pores, according to the model proposed by Schmidt et al. (2012 ). Our results enable us to estimate the heating temperatures used by Chassey artisans to ≈ 230°C. We also propose the 'pressure cooker' model to explain the migration of liquid water in flint nodules heated to 230°C. Then, we discuss the ability of a particular type of flint to be heat‐treated, and hence its value for Neolithic society, which depends on: (1) the amount of LS chalcedony that ensures the water release at relatively low temperature; and (2) on the total volume of porosity available to store the dehydration water.